Design and Parametric Optimization of a Double-Sided Linear Induction Motor for Hyperloop Pod - Goksun, Bahaddin; Sen, Ismet; Kuzucu, Musap; Ergun, Bati Eren; Kocaarslan, Ilhan; Gulbahce, Mehmet Onur (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The hyperloop idea, which is one of the most ecofriendly, low-carbon emissions, and fossil fuel-efficient modes of transportation, has recently become quite popular. In this study, a double-sided linear induction motor (LIM) with 500 W of output power, 60 N of thrust force and 200 V/38.58 Hz of supply voltage was designed to be used in hyperloop development competition hosted by the scientific and technological research council of turkey (TÜBİTAK) rail transportation technologies institute (RUTE). In contrast to the studies in the literature, concentrated winding is preferred instead of distributed winding due to mechanical constraints. The electromagnetic design of LIM, whose mechanical and electrical requirements were determined considering the hyperloop development competition, was carried out by following certain steps. Then, the designed model was simulated and analyzed by finite element method (FEM), and the necessary optimizations have been performed to improve the motor characteristics. By examining the final model, the applicability of the concentrated winding type LIM for hyperloop technology has been investigated. Besides, the effects of primary material, railway material, and mechanical air-gap length on LIM performance were also investigated. In the practical phase of the study, the designed LIM has been prototyped and tested. The validation of the experimental results was achieved through good agreement with the finite element analysis results.
Keywords: finite element analysis (fea); linear induction motor (lim); Electrical engineering. Electronics. Nuclear engineering; motor design; hyperloop; TK1-9971